The Role of Stakeholders in CSR Reporting of Non-Listed Banks - Gulenko, Maryna; Kohlhase, Saskia; Kosi, Urska (Accounting in Europe)
We investigate the role of stakeholders in the CSR reporting of non-listed savings banks in Germany. They are established by municipal trustees and serve clients in their distinct operating area. Reporting discretion under the Non-Financial Reporting Directive may lead to variation in CSR reporting due to differences in sustainability interests of banks’ stakeholders and CSR governance (e.g. existence of a CSR manager). We document that the CSR reports and specific CSR dimensions are intensely associated with the existence of strong CSR governance and to a lesser extent with the interests of municipal trustees and bank clients. However, the associations with these stakeholders are predominantly present in banks with strong CSR governance. Our findings inform policy discussions about detailed CSR disclosure requirements (e.g. the European Sustainability Reporting Standards) and extension of reporting scope to firms with regional orientation and absence of typical shareholders.

"Kirchentag" - An example of religious happenings as places for the formation of faith in a world full of diversity - Schroeter-Wittke, Harald (Religious Diversity and Global Concerns)

Intertwining theory and practice: Design of planning phases in PD training to support effective teacher planning processes - Knaudt, Katharina; Herold-Blasius, Raja; Selter, Christoph (Proceedings of the Fourteenth Congress of the European Society for Research in Mathematics Education (CERME14)

Fostering Knowledge Facets of the TPACK Framework Through Designing Digital Mathematical Escape Games – A Qualitative Content Analysis of Pre‑Service Teachers’ Self‑Reported Learnings and Challenges - Herold-Blasius, Raja; Gruhn, Katrin; Kleinschmidt, Vera; Thurm, Daniel; Tusche, Carina (International Journal of Science and Mathematics Education)

TPACK learning paths of pre-service teachers when designing digital mathematical escape games - Herold-Blasius, Raja; Kleinschmidt, Vera (Proceedings of the Nineteenth ERME Topic Conference: Connecting the Learning of Mathematics Teaching to Practice)

Digitale Escape Games in der Hochschullehre – Seminarkonzept - Herold-Blasius, Raja; Kleinschmidt, Vera

Temporal causal feature selection for robust machine learning modelling of data center operations - Zapata Gonzalez, David Ricardo; Meyer, Marcel; Zalipski, Kevin; Müller, Oliver (Applied Energy)

Defining Islamic Comparative Theology
Over the last decades, Comparative Theology has established itself in varying methodological ways while considering the reality and plurality of religions. Although Comparative Theology can be a confessional or a non-confessional endeavor, most protagonists and theorists have been Western Christians. This could lead to the conclusion that Comparative Theology is in fact a Christian undertaking and implicitly or explicitly bound to conceptions like Christology. Furthermore, it could be argued that there is a certain asymmetry of power in the discourse between religions when the parameters of Comparative Theology are defined mainly by Christian theologians. This volume aims to be the first step to programmatically and conceptionally explore the possibility of a genuinely Islamic Comparative Theology in a constructive endeavor. This endeavor should neither be misunderstood as an apologetic questioning of the status quo in Comparative Theology nor as a project that deconstructs Comparative Theology. Rather, by searching for new approaches from the Islamic traditions it opens up ways and forms of learning, hermeneutically complementary with prominent attitudes, methods in Comparative Theology.
Keywords: Comparative Theology; Islamic Theology; Islamic Comparative Theology

Chapter 5 Covenant Theology in the Qur’an—Challenges and Insights for Comparative Theology from a Muslim Perspective - Ghaffar, Zishan (Defining Islamic Comparative Theology)
Keywords: Covenant Theology; Qur'an; Comparative Theology; Islamic Comparative Theology

History and political Theology: The term khalīfah in the Qur’an - Ghaffar, Zishan (Journal of the International Qur’anic Studies Association)
This article examines the use of the Arabic term khalīfah in the Qur’an through the lens of its implicit historical-political theology. To achieve this, the study employs a comparative analysis of the concept of vicarious kingship within the Syriac tradition. The findings suggest that the Qur’an rejects the notion of a historical replacement or substitution of believing individuals or groups with new ones. Furthermore, it challenges the framework of a political theology that envisions the typological and eschatological fulfillment of messianic rulership. Instead, the term khalīfah primarily emphasizes the inherently political nature of humanity, in which each individual is continuously accountable to their Creator.

Empirische Studien zur Demokratiebildung im Lehramtsstudium in Nordrhein-Westfalen - Wehde, Janis

Local strong solutions in a quasilinear Moore-Gibson-Thompson type model for thermoviscoelastic evolution in a standard linear solid - Claes, Leander; Winkler, Michael (Nonlinear Differential Equations and Applications NoDEA)

Selection of the mini- and micro-channels geometry for improved heat recuperation in specific industrial conditions - Kapustenko, Petro; Tovazhnyanskyy, Leonid; Arsenyeva, Olga; Riese, Julia; Varbanov, Petar Sabev (International Journal of Thermal Sciences)

Building Bridges – Partizipation und Reflexion mit der LEGO® SERIOUS PLAY®-Methode fördern - Breuing, Friederike

Error estimates for $A$-stable backward difference full discretizations of Willmore flow of closed surfaces - Bullerjahn, Nils; Kovács, Balázs (ArXiv)

The Lord’s Prayer and its place in the London Underground. Reflections on religious diversity and a parody based on a central sacred text - Breckner, Anne (Religious Diversity and Global Concerns)

Die Widerruflichkeit der Verbraucherbürgschaft – a never ending story - Bartlitz, David (JuristenZeitung)
Die Frage, ob bei einer Verbraucherbürgschaft, die in einer Außergeschäftsraumsituation abgegeben worden ist, ein Wider-rufsrecht besteht, ist seit nunmehr 30 Jahren umstritten. Der BGH hatte im Jahr 2020 in einem Grundsatzurteil das Widerrufsrecht abgelehnt - nur neun Monate vor der erneuten Ände-rung des für diese Frage entscheidenden § 312 BGB. Der Beitrag zeigt, dass die Abgabe einer Bürgschaftserklärung notwendigerweise mit der Bereitstellung personenbezogener Daten verbunden ist. Dies eröffnet aufgrund des überobligatorisch weit gefassten Tatbestands des neuen § 312 Abs. 1a BGB den Anwendungsbereich des Verbrauchervertragsrechts und begründet damit das Widerrufsrecht nach § 312g BGB.

Influence of negative ions on the stoichiometry and structure of carbon nitride films deposited by reactive magnetron sputtering - Wieschhoff, Christian; Theile-Rasche, Chantal; Wang, Fuzeng; Prib, Michael; Moldt, Viktoria Daniela Dorothea; Grundmeier, Guido; Salas, Nieves López; de los Arcos de Pedro, Maria Teresa (Journal of Applied Physics)
Magnetron-sputtered CNx thin films are primarily employed as hard, low-friction protective and tribological coatings, as solar cells, and for catalytic applications. Lower growth rates and a reduced N content, favoring graphitic sp2 structures, hinder industrial scalability due to prolonged deposition times and produce softer, less dense films with inferior hardness, elasticity, and wear resistance. Carbon nitride films deposited by magnetron sputtering exhibit growth behavior strongly influenced by plasma–surface interactions. However, nitrogen resputtering and reduced film growth rates are commonly attributed to chemical etching by positive ions. We propose an additional, unreported power-dependent mechanism involving negative ions formed at the carbon target. These ions are accelerated through the plasma sheath, reaching the substrate with high kinetic energy and inducing both chemical and physical resputtering. This effect is localized to the geometrical projection of the target, as shown by spatially resolved analysis: ellipsometry reveals thickness reduction, and x-ray photoelectron spectroscopy and Raman spectroscopy indicate nitrogen depletion within this region. Correlation between stoichiometry and structural signatures confirms the decisive role of negative ions in modifying the film composition and microstructure. At the same time, the composition of the gas mixture exerts only a minor effect.

Role of Irradiance in Light-Activated In 2 O 3 Gas Sensors: Why More Light Is Not Always Better - Voth, Sven; Zhao, Zhenyu; Baier, Dominik; Glass, Alexandra; Elgabarty, Hossam; Sandberg, Oskar J.; Grundmeier, Guido; Tiemann, Michael; Smått, Jan-Henrik; Anttu, Nicklas; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian (ACS Sensors)

Influence of deposition temperature and thickness of ALD-TiO2 on planar perovskite solar cell performance - Qudsia, Syeda; Weiss, Alexander; Sirkiä, Saara; Wang, Fuzeng; Rosqvist, Emil; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Halme, Janne; Kemell, Marianna; Smått, Jan-Henrik (Applied Surface Science)